EFEKTIVITAS PENERAPAN MODEL PEMBELAJARAN REALISTIC MATHEMATICS EDUCATION (RME) TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIKA SISWA SMP SWASTA ADVENT BARUS - Lubis, Roslian; Ahmad, Marzuki; Simanullang, Syahtija (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2023)
Abstract This study aims to determine whether there is an effectiveness of applying RME learning model on the mathematical communication skills at the eighth grade students of SMP Swasta Advent Barus. The research used an experimental method by applying one group pretest posttest design. The sample of this study is taken by using total sampling technique, the eleventh grade students of SMP Swasta Advent Barus which includes 35 students. Observation and tests are used in collecting the data. Observation sheets show the applying of RME learning model has an average of 2.93 (good category) while students' mathematical communication skills before applying RME learning model has an average of 64.70 (enough category) and after applying RME learning has an average of 72.13 (good category). Furthermore, based on the calculation of the t-test (SPSS of version 2017) it shows the value of Sig. (2-tailed) is 0.000 < 0.005, classical completeness is 51.43% and the N-Gain value shows 0.27 (low category). It means, there is any effectiveness of appying RME learning model on students' mathematical communication skills in the low category at the eighth grade students of Barus Adventist Private Junior High School.